2019
DOI: 10.3390/w11081567
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Perspective Changes in Crop Irrigation Requirement Caused by Climate and Agriculture Land Use Changes in Rechna Doab, Pakistan

Abstract: Climate change and agriculture land use changes in the form of cropping patterns are closely linked with crop water use. In this study the SDSM (statistical downscaling model) was used to downscale and simulate changes in meteorological parameters from 1961 to 2099 using HadCM3 General Circulation Model (GCM) data under two selected scenarios i.e., H3A2 and H3B2. Results indicated that Tmax, Tmin, and wind speed may increase while relative humidity and precipitation may decrease in the future under both H3A2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 59 publications
5
22
0
Order By: Relevance
“…Thus, applying suitable downscaling models can improve the results of climate change studies [5][6][7][8]. LARS-WG, as one of the downscaling models, is used for the simulation of climate information under current and future circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, applying suitable downscaling models can improve the results of climate change studies [5][6][7][8]. LARS-WG, as one of the downscaling models, is used for the simulation of climate information under current and future circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Reinecke et al (2020) reported that the uncertainty range in climate change is large, and predictions with confidence with groundwater recharge can only be made for a specific region. Climate change decreases cotton yield from 699 to 534 kg.ha -1 and elevates cotton irrigation requirement from 960.1 to 1048.9 mm in Pakistan (Arshad et al 2019;Abbas 2020;Rehman 2021). However, from T1 to T6, cotton yield per hectare increased (Fig.…”
Section: Impact Of Climate Change On Groundwater Rechargementioning
confidence: 99%
“…From the historical data analyses, it is clear that canal water supply is on the decline in Rechna Doab, along with significantly decreasing rainfall, especially in the middle and lower regions. On the other hand, according to [75], crop irrigation requirements would significantly increase in the coming years. The major reasons are elevated temperatures and decreasing air humidity.…”
Section: Irrigation Source and Consumptive Water Usagementioning
confidence: 99%